EFFECT OF SOWING DATE, SEEDING RATE, AND PLANTING METHOD ON 1000-GRAIN WEIGHT AND GRAIN YIELD OF BUCKWHEAT UNDER IRRIGATED TYPICAL SIEROZEM SOIL CONDITIONS - Isroilov B.A. (NEW APPROACHES IN EDUCATION: PEDAGOGY, INNOVATION, AND DEVELOPMENT, 2025)
This study investigated the influence of sowing dates, seeding rates, and planting methods on grain quality and yield components of buckwheat (Fagopyrum esculentum Moench) cultivated as a second crop under irrigated typical sierozem soil conditions. The primary objective was to identify optimal agronomic practices for maximizing 1000-grain weight and grain yield. The results demonstrated that grain plumpness and weight were fundamentally linked to the plant’s nutritional area. The highest 1000-grain weight values (24.0-24.3 g) were consistently achieved under early sowing dates (June 20 and July 1) with lower plant densities, specifically in treatments using the single-row method at 1 million seeds/ha and the double-row method at 2 million seeds/ha. Across all planting methods, superior grain weight was associated with early sowing. Conversely, the maximum grain yield of 22.4 q/ha was obtained under a high-density planting regime: sowing on June 20 using the triple-row method at a seeding rate of 3 million seeds/ha. This indicates a trade-off between individual grain quality (weight) and total yield per unit area, mediated by sowing date and plant density. These findings provide a scientific basis for tailoring buckwheat cultivation strategies to specific production goals under irrigated semiarid conditions.